PENGARUH PENERAPAN METODE KOOPERATIF TIPE TEAMS GAME TOURNAMENT TERHADAP HASIL BELAJAR GEOGRAFI KELAS X SMA NEGERI 3 GUNUNGSITOLI - Christian Anugerah Fajar Putra Zebua; Syafri Anwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine how the effect of the Application of Teams Game Tournament Type Cooperative Method on Geography Learning Outcomes of Class X SMA Negeri 3 Gunungsitoli. This research uses the Quasy Experiment method with a quantitative approach and this research design uses Pre-test - Post-test Control Group Design. The research sample was class X students of SMA Negeri 3 Gunungsitoli in the 2024/2025 academic year with a total of 351 students from 10 classes. The research sample consisted of class X-5 as the control class and class X-1 as the experimental class which was selected using purposive sampling technique. Data collection techniques include observation, documentation, and tests. The results showed that the average Pre-test of the experimental class was 58.03 and Post-test 87.14, while the control class obtained Pretest 61.65 and Post-test 72.09. There was a significant increase in the experimental class. The results of the Paired Sample T-Test test showed a significance level (sig) of 0.001. Because this significance value is smaller than 0.05, Ho is rejected and Ha is accepted.